Cross-cultural reliability and validity of a scale to measure firm entrepreneurial orientation - Knight, Gary A. (Journal of Business Venturing, 1997)
This study presents a foreign language version of a popular scale for measuring entrepreneurship and tests the instrument's utility in cross-cultural settings as a means of validating it for use abroad. Entrepreneurship refers to the pursuit of creative or novel solutions to challenges confronting the firm, including the development or enhancement of products and services, as well as new administrative techniques and technologies for performing organizational functions. Entrepreneurship is a fundamental posture, instrumentally important to strategic innovation, particularly under shifting conditions in the firm's external environment, and is applicable to any firm, regardless of its size and type. Scholars note that entrepreneurial activity is critical because it stimulates superior performance and may well be the key fundamental element in the procurement of advantages relative to competitors. Researchers have developed a popular scale for measuring entrepreneurship at the firm level, which has been found to be highly valid and reliable. This scale (the “ENTRESCALE”) examines eight items reflecting the innovative and proactive disposition of management at a given firm. However, as the ENTRESCALE's measurement properties have never been comprehensively assessed in a cross-cultural setting, the instrument lacks strong evidence of international validity and reliability. Accordingly, the cross-cultural correspondence between the ENTRESCALE and the construct it is supposed to measure is unknown, as is the extent of its utility to international practitioners. This situation reflects a problem common to measuring instruments developed in the United States and is particularly troublesome for scales intended to measure foreign phenomena of interest in international business. The researcher who assumes that a scale developed at home will function with equal efficacy abroad is most likely asking for trouble. There is a risk that such assumptions will lead to invalid inferences, an outcome potentially disastrous for the practitioner seeking to design appropriate strategies for international success. Sound measures of entrepreneurship are especially critical for managers attempting to understand the construct's cultural dynamic, at both the organizational and country levels, within subsidiaries, agencies, and other such entities presently representing or offering to represent the firm's interests abroad. By understanding the entrepreneurial dynamic in foreign settings, the multinational firm may be able to structure operations in ways that better suit existing local conditions and thereby avoid potentially adverse consequences. Further, it is useful to discern, by means of national studies, the entrepreneurial characteristics of management at firms, including existing or potential competitors, across entire countries. As a means of addressing this issue, this study seeks to test the measurement properties of the ENTRESCALE using samples of English- and French-speaking managers. Results indicate that the scale performs well in terms of both reliability and validity and possesses a unique factor structure. In concrete terms, this implies that the ENTRESCALE is suitable for measuring the entrepreneurship construct abroad. It is hoped that these results will: (1) contribute to improving future research endeavors of scholars studying the role of entrepreneurship in the increasingly global environment of business; (2) provide practitioners with a scale that can be used to measure the extent of entrepreneurial orientation among main operations, subsidiaries, and (potential) partner firms in foreign lands; and (3) raise the standard by which measuring instruments are designed and used for research in cross-cultural contexts.